Introversi dan Penguasaan Berbahasa Arab Aktif - Rifqi Aulia Rahman (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2019)
Introversion is the self-closing attitude with others. This attitude arises not as timid and inferior in front of them, but it is intense and comfortable with himself and feels enough of his qualities. Communication becomes a precious activity because the activity requires a subject outside itself. In the meantime, understanding the Arabic language requires someone to communicate effectively with others, verbally or in writing. The majority of teachers or language instructors in the class, have a major task, meant to make students skilled in communicating. Good value for students who ask a lot of questions, answers, discuss, brainstorm, do jobs, etc. Consequently, introversion is one of the psychological and social problems of language learning, especially for Arabic.